Motorcycle starter via Bluetooth / Abu Syaiful Kyairi Abu Hassan - Abu Hassan, Abu Syaiful Kyairi (2006)
Bluetooth technology is how mobile phones, computers, and personal digital assistants (PDA), not to mention a broad selection of other devices, can be easily organized using a short-range wireless connection. Using this technology, users can have all mobile and fixed computer devices be totally coordinated. Nowadays, Bluetooth technology has become popular and grows up with variety of usage to the users. This thesis concentrates on the study about the Bluetooth concept generally and the capability of the Bluetooth in communication. Therefore, through this thesis we developed the prototype that makes the Bluetooth technology to start a motorcycle using Bluetooth with PIC devices and Palm Operating System application. The application has been developed using C programming and assembly language. Through this thesis also, the development process follows the System Development Life Cycle (SDLC). In the end of the development, the prototype of this device is come out and readily to be tested. The prototype generally involved in discovers the Bluetooth signal and send a character to the PIC circuit board. When the PIC circuit board receives the signal, it will activate the motorcycle starter. Only specified character can activate the motorcycle starter by PIC circuit board. This thesis actually is just the beginning where more resource, energy and time are needed in order to make this device perfect. Hopefully, this thesis can create an opportunity to go further and deeper in the world of wireless technology within Bluetooth environment.